Early detection of neurodevelopmental disorders in African children living in informal settlements in Nairobi - Maurizio Bonati; Rita Campi; Maria Paola Canevini; Giulia Segre; Cecilia Cargnelutti; Carlotta Bersani; Washington Njogu; Elisa Roberti; Maria Vittoria De Vita; Gianfranco Morino (BMJ Publishing Group, 2023)
Background Children in low-income and middle-income countries (LMICs) are at a substantially increased risk of delayed physical, emotional and sociocognitive outcomes, with consequential neurodevelopmental disorders. Evidence based, cost-effective and culturally appropriate screening tools are recommended for early identification of developmental disorders.Methods The present study aims to assess the feasibility of early screening for neurodevelopmental disorders in children living in informal settlements in Nairobi, Kenya (Korogocho). The selected tools (ie, the CDC checklist and the Modified Checklist for Autism in Toddlers, Revised (M-CHAT-R)), widely used in high-income countries, are applied in two different populations: one from Kenya (LMIC) and one from Italy, to compare the different scores.Results Of 509 children screened, 8.6% were classified at-risk based on the results of the screening tools. Significant risk factors are history of low birth weight and Apgar score, presence of neurological disorders, malnutrition and/or rickets, younger age of the child and older age of the mother. Caesarean section delivery, first pregnancy and mothers' older age were common risk factors among the Kenyan and the Italian samples. The Italian sample had a significantly greater rate of missed milestones.Conclusions Our data demonstrate the feasibility of using the CDC and M-CHAT-R tools in informal settlement dwellers. Further studies are needed to explore the opportunity for early diagnosis of developmental disorders in LMICs.